THE IMPACT OF EARNINGS PER SHARE (EPS) AND DIVIDEND PAYOUT RATIO (DPR) ON DIVIDEND YIELD OF COMPANIES LISTED IN THE JAKARTA ISLAMIC INDEX - Hayu Yolanda Utami; Defriko Gusma Putra; Mona Amelia (JURNAL ECONOMICA : Research of Economic And Economic Education, 2026)
This study aims to examine the effect of Earnings Per Share (EPS) and Dividend Payout Ratio (DPR) on Dividend Yield of companies listed in the Jakarta Islamic Index (JII) on the Indonesia Stock Exchange during the 2021–2025 period. The study is motivated by the increasing importance of dividend yield as an indicator of investment returns in the Islamic capital market, alongside inconsistent findings from previous studies regarding the influence of corporate profitability and dividend policy on dividend yield. This research employs a quantitative explanatory approach using secondary data obtained from the annual reports and financial statements of companies listed in the Jakarta Islamic Index. The sample consists of 15 companies selected through purposive sampling, resulting in 75 panel data observations over the five-year study period. Data analysis was conducted using panel data regression with the Fixed Effect Model (FEM) selected as the most appropriate estimation model. The empirical findings indicate that Earnings Per Share has a positive and significant effect on Dividend Yield, suggesting that higher corporate profitability enhances investors' expectations of dividend payments. Furthermore, Dividend Payout Ratio also has a positive and significant effect on Dividend Yield, indicating that companies distributing a larger proportion of earnings as dividends provide higher returns to shareholders through dividend income. The findings support Signaling Theory, which explains that profitability and dividend policy function as positive signals regarding a firm's financial performance and future prospects. This study contributes to the literature on Islamic capital markets by providing recent empirical evidence on the determinants of dividend yield among Sharia-compliant companies listed in the Jakarta Islamic Index. Practically, the findings provide useful insights for investors in selecting dividend-oriented Islamic stocks and for corporate managers in formulating sustainable dividend policies.